A Finite Element Analysis of Bearing Resistance of Timber Loaded through a Steel Plate - Awaludin A.; Hirai T.; Hayashikawa T.; Leijten A.J.M. (Civil Engineering Dimension, 2012)
Decrease projected length of bolts due to bending deformation in timber joints compresses the steel washers onto timber member and increases lateral resistance of the joints. As this lateral strength increase primarily depend on bearing characteristics of timber beneath the steel washers, a finite element analysis was performed to predict their bearing-embedment behavior. A 3-D finite element model consisting of 8-node solid and contact pair elements was developed using ANSYS assuming an anisotropic plasticity model for timber and an elastic-perfectly plastic model for the washers. Material constants for both steel washer and timber member were obtained from previous test data. The results of the analysis were in good agreement with the experimental load-embedment curves as well as the analytical curves obtained in a previous study based on a rigid-body-spring-model. The same approach was also used to evaluate the effective bearing length (under uniform compression) of a 50 mm depth timber block partially compressed.